PABRIK SODIUM SULFAT DEKAHIDRAT DARI SODIUM CHLORIDE DAN ASAM SULFAT DENGAN PROSES MANNHEIM - Purwaningsih, Dian Yanuarita; Mulya, Jaya Hadi (Institut Teknologi Adhi Tama Surabaya, 2024)
At the end of 2019, the COVID-19 pandemic hit the world, which had several effects on various sectors, one of which made several industrial sectors suffer heavy losses and even bankruptcy. The industrial sector needs household goods, such as soap and detergent, among the most needed items during the Covid-19 pandemic. To produce these hygiene items, the industrial sector requires various raw materials, one of which is Sodium sulfate (Na2SO4). Sodium sulfate is processed using the Mannheim process through reaction, crystallization, and drying stages. The designer plans to build a plant with a capacity of 20,000 tons/year in the industrial area of Lamongan, East Java. The raw materials used consist of sulfuric acid and sodium chloride. The utility unit consists of a water supply unit, steam supply unit, power generation unit, fuel supply unit, and cooling supply unit. The company's business entity is a Limited Liability Company (PT) using a line and staff organizational structure with 150 employees. The employee work system is based on the division of working hours consisting of shift and non-shift employees. The researchers produced several results of economicanalysis: Fixed Capital Investment (FCI) value of Rp. 195,180,724,917, Working Capital Investment (WCI) value of Rp. 34,443,657,338, Total Cost Investment (TCI) value of Rp. 229,624,382. 255, then the Total Product Cost (TPC) value is Rp. 441,103,560,855, and the Total Sale (TS) value is Rp. 522,048,972,696, Internal Rate of Return (IRR) of 35.98%, Pay Out Time (POT) for 3.15 years, and Break-Even Point (BEP) value of 36.40%. Based on the above evaluation results, the Sodium sulfate decahydrate plant from Sulfuric acid and Sodium chloride by Mannheim process is feasible.